2019
DOI: 10.3168/jds.2018-15298
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Replication of genome-wide association studies for milk production traits in Chinese Holstein by an efficient rotated linear mixed model

Abstract: Milk is regarded as an important nutrient for humans, and Chinese Holstein cows provide high-quality milk for billions of Chinese people. Therefore, detecting quantitative trait nucleotides (QTN) or candidate genes for milk production traits in Chinese Holstein is important. In this study, we performed genomewide association studies (GWAS) in a Chinese Holstein population of 6,675 cows and 71,633 SNP using deregressed proofs (DRP) as phenotypes to replicate our previous study in a population of 1,815 cows and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(36 reference statements)
3
15
0
Order By: Relevance
“…This region contains several genes including MIR2308, CYHR1, FOXH1, COMMD5, TONSL, PPP1R16A, MFSD3, LRRC24, C14H8orf33, RECQL4, ARHGAP39, RPL8, GPT, LRRC14, ZNF34, C14H8orf82, ZNF7 and KIFC2. The association of genes including TONSL, PPP1R16A, FOXH1, ARHGAP39, CYHR1 and ARHGAP39 with milk yield and milk composition has been reported in previous studies (Buitenhuis et al, ; Nayeri & Stothard, ; Ning et al, ; Wang et al, ). Nayeri et al () reported that highly significant SNP for milk yield in Canadian Holsteins were mapped inside genes including CPSF1 , DGAT1 , TONSL , CYHR1 , FOXH1 and PPP1R16A .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This region contains several genes including MIR2308, CYHR1, FOXH1, COMMD5, TONSL, PPP1R16A, MFSD3, LRRC24, C14H8orf33, RECQL4, ARHGAP39, RPL8, GPT, LRRC14, ZNF34, C14H8orf82, ZNF7 and KIFC2. The association of genes including TONSL, PPP1R16A, FOXH1, ARHGAP39, CYHR1 and ARHGAP39 with milk yield and milk composition has been reported in previous studies (Buitenhuis et al, ; Nayeri & Stothard, ; Ning et al, ; Wang et al, ). Nayeri et al () reported that highly significant SNP for milk yield in Canadian Holsteins were mapped inside genes including CPSF1 , DGAT1 , TONSL , CYHR1 , FOXH1 and PPP1R16A .…”
Section: Discussionsupporting
confidence: 59%
“…This region contains several genes including MIR2309, MIR1839, OPLAH, HGH1, GRINA, PARP10, MAF1, SHARPIN, CYC1, GPAA1, MROH1, EXOSC4 and SPATC1. The association of genes including OPLAH, GRINA and MF1 with milk yield and lactation performance has been reported in previous studies (Kolbehdari et al, 2009;Wang, Ning, Liu, Zhang, & Jiang, 2019); however, the association of the remaining identified genes inside this region with lactation performance in dairy cows has not been reported previously.…”
Section: T a B L E 5 Gene Ontologies (Go)mentioning
confidence: 64%
“…Genetic improvement can gradually induce smaller but permanent trait modifications [1], and genetic analyses have shown heritable variations in milk, fat and protein yields, and fat and protein percentages of bovine [2]. Genome-wide studies in dairy cows have allowed researchers to detect quantitative trait locus (QTL) harboring candidate polymorphic genes that are involved in milk production [3,4,5]. Moreover, studies have shown that the single nucleotide polymorphisms (SNPs) in the genes clearly influenced the milk yield and composition in Holsteins [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additional large set of candidate genes (LRRC24, LRRC14, RECQL4, HEATR7A, MFSD3, GPT, PPP1R16A, FOXH1, CYHR1, SLC39A4, CPSF1, ADCK5, FBXL6, BOP1, SCRT1, DGAT1, GPAA1, EXOSC4, PARP10, HSF1, OPLAH, and GRINA), associated with milk production traits in Kholmogor cattle was found on BTA 14. These genes were shown to be involved in regulation of milk fatty acid composition [113][114][115][116], milk yield [117,118], milk fat yield, and milk fat percentage [119][120][121][122][123]. In contrast to Kholmogor cattle, we identified only two candidate genes on BTA 5, which were associated with milk production traits in Yaroslavl cattle, including TMCC3 and DDX10 [124,125].…”
Section: Plos Onementioning
confidence: 81%